2012
DOI: 10.2478/v10222-011-0039-z
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profile of Muscles of Freshwater Fish from Olsztyn Markets

Abstract: The aim of the present study was to determine the profi le of fatty acids in muscle lipids of freshwater fi sh: carp (Cyprinus carpio L.), rainbow trout (Oncorhynchus mykiss Walb.), bream (Abramis brama L.) and tench (Tinca tinca L.) from markets of Olsztyn (north-eastern Poland). Separation and identifi cation of fatty acids were made using gas chromatography. The content of some fatty acids varied among species. Generally, palmitic acid (15.6%-19.5%) was the most abundant saturated fatty acid (SFA). The main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 17 publications
(17 reference statements)
7
10
0
Order By: Relevance
“…In similar manner, the total n-6 FA contents of Luczynska et al (2012) for the above species were found to be ranging as 10.8 + 3.5, 8.4 ± 0.5, 10.5 ± 1.4 and 12.9 + 1.8, respectively.…”
Section: 6supporting
confidence: 56%
See 2 more Smart Citations
“…In similar manner, the total n-6 FA contents of Luczynska et al (2012) for the above species were found to be ranging as 10.8 + 3.5, 8.4 ± 0.5, 10.5 ± 1.4 and 12.9 + 1.8, respectively.…”
Section: 6supporting
confidence: 56%
“…15.99 ± 0.80 to 32.54 ± 3.77, which were also found to be quite lower than that of (Luczynska et a!, 2012). In the group of MUFA of this present study, Oleic acid (C 18:1 n-9) was the predominant FA, which also consistent and agreeable with the findings of (Luczynska ci at, 2012).…”
Section: 6mentioning
confidence: 57%
See 1 more Smart Citation
“…For the comparison, the Western diet is now dominated by n ‐6 PUFA, with a n ‐3/ n ‐6 ratio of 0.06 (Özoğul et al, ). In the study of Łuczyńska, Paszczyk, Borejszo, and Tarkowski () this value for carp was 0.4, and according to Kołakowska, Szczygielski, Bienkiewicz, and Zienkowicz () it was even lower (0.1). Thus, Usydus et al () noticed that carp is not a species of fish that should be recommended to people suffering from coronary heart disease, because of its relatively low concentrations of EPA and DHA and a low ratio of n ‐3/ n ‐6 acids.…”
Section: Fatty Acidsmentioning
confidence: 93%
“…Monounsaturated fatty acids (MUFA) were found in rainbow trout fish oil, bream fish oil and tench fish oil of 35.9, 35.8 and 38.3%, respectively (Luczynska et al, 2012). Monounsaturated fatty acids (MUFA) were present in Malabar Red Snapper fish oil, trevally fish oil and Spain Mackarel at the concentrations of 141.8, 286.8, 70.6 mg/100 g, while for polyunsaturated fatty acids (PUFA) at the concentrations of 724.7, 869.6, and 322.8 mg/100 g, respectively (Nurnaida et al, 2013).…”
Section: Microencapsulation Of Fish Oil On the Fatty Acids Omega 3 mentioning
confidence: 99%